Sustainable agriculture and the environment in the humid tropics - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
Sustainable agriculture and the environment in the humid tropics a report by the National Research Council, 1993 720pp ISBN 0 309 04749 8 Hbk price $49.95 National Academy Press 2101 Constitution Avenue, NW Box 285, Washington, DC 20055 USA